Analisis Perbandingan Quality of Service LTE Telkomsel Berdasarkan Parameter KPI - Rizky Nuriza Fabian (LPPM Poltek ST Paul, 2021)
Abstract Key Performance Indicator (KPI) analysis aligned with Quality of Service is a parameter to evaluate cellular network performance. Telkomsel as one of the cellular operators applies quite strict parameters to always improve its network performance. The parameters discussed in this study are used to support network performance including accessibility, retention, and integrity. These parameters were analyzed to compare Frequency Division Duplex (FDD) and Time Division Duplex (TDD) technologies on Telkomsel's LTE network. As a result, Quality of Service (QoS) which has been aligned with the Key Performance Indicator parameters compares the performance between LTE TDD and FDD networks. LTE TDD has an average failure percentage of 0.073%, smaller than LTE FDD which has a higher failure percentage of up to 0.159%. Keywords: Key Performance Indicator (KPI), BTS, QoS, LTE